Pemetaan Wisatawan Domestik Pada Destinasi Wisata Di Provinsi Jawa Timur - Sri Hartini; Aji Sudarsono; Sukaris Sukaris (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2020)
Backgorund - East Java is one of the provinces in Indonesia with a very diverse potential for tourist attraction. The tourist attraction is divided into 3 (three) categories, namely nature, culture and special interests. The growth of tourists in East Java has increased over the last few years, placing East Java as one of the provinces with the largest domestic tourist arrivals in Indonesia. One way to sustain growth is by mapping. Aim - This study aims to map domestic tourists (demographic and geographical aspects) in East Java to tourist destinations. The results of the mapping are expected to provide information in determining the target market and can be used as a reference in developing tourism according to tourist needs. Design / methodology / approach - The research subjects are domestic tourists visiting several tourist destinations in East Java. This research is a type of quantitative research. Data collection tool in the form of questionnaires with survey techniques through interviews with respondents. The data collected was then tested for association using crosstabs with the Creamers v method and analyzed using the correspondence analysis technique. Finding - The results showed there were differences in the determination of the category of tourist attractions visited by tourists based on demographic and geographical aspects where the presentation of East Java Province research results was divided into 5 (five) regions. Research implication - The results of this study can be used as a reference for stakeholders in designing development and development policies and tourism marketing programs.